ANALISIS RASIO LIKUIDITAS, RASIO PROFITABILITAS DAN SALES GROWTH PRA DAN PASCA BERLAKUNYA UNDANG-UNDANG BADAN PENYELENGGARA JAMINAN SOSIAL - Stevany Febreany (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
The National Health Insurance Program is a mandatory social health insurance. The problem is experienced by pharmaceutical companies where product prices in the era of National Health Insurance have been determined by the government making the price below the company's production costs plus the deficit experienced by the Social Security Administering Agency (BPJS) resulting in companies having to operate on a low profit and low margin. The purpose of this study is to identify financial conditions in the pre and post era of the National Health Insurance. The research method used is descriptive quantitative research method with financial ratio comparison analysis tools, namely liquidity ratios calculated through the cash ratio, profitability ratios calculated through net profit margins and sales growth in the financial statements of PT Hexpharm Jaya Laboratories from 20092013 and 2014- 2018. The results showed that the liquidity ratio calculated by cash ratio and profitability ratio calculated by net profit margin was lower after post-National Health Insurance compared to the era before National Health Insurance. Sales growth experienced growth after the National Health Insurance.